ANALISIS KEBUTUHAN TENAGA PERAWAT BERDASARKAN BEBAN KERJA DENGAN MENGGUNAKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DAN WORK SAMPLING - Putri Julia; A. Jabbar M. Rambe; Dini Wahyuni (Jurnal Teknik Industri USU, 2014)
The study was conducted in private hospital in the city of Binjai, which has 12 policlinic. Outpatient installation have 2 nurses and often ask for additional nurses from the emergency unit when a patient comes to the same outpatient polyclinic at 3 polyclinic or more. In addition the number of visitors has increased 2.5% in 2011 and 3.1% in 2012 while the number of nurses are fixed. Therefore need to analyze the needs of nurses based on workload to know the needs of nurses. Work Sampling method to determine the usage patterns of working time and Workload Indicator Staff Need ( WISN ) for the calculation of energy need. The results of work sampling observations indicate that the two nurses had worked well because average 93% productive time. The results of calculations by the method of Workload Indicator staff Need ( WISN ) note the need for nurses is 2 people while the analysis it is necessary to the addition of 1 nurse.